Laserunterstütztes Biegen höchstfester Mehrphasenstähle - Pitz, Matthias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2005)
The use of high strength steel has a substantial potential far the lightweight construction, however the forming of high strength steel is very difficult. In this book it is represented, how the forming limits of the high strength multi-phase steel can successfully be increased by a laser assisted bending proces